Determinants of Student Loyalty: A Case Study of Chongqing University of Arts and Sciences - Zuo, Yuting (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study investigated the influence of five independent variables, student satisfaction, image, commitment, service quality, and university sustainability practices, on the dependent variable, student loyalty. It also assessed differences between pre- and post-strategic plan implementations. Research design, data and methodology: A mixed-methods approach was adopted. Instrument validity was confirmed using the Index of Item-Objective Congruence (IOC), and reliability was ensured through a pilot test with Cronbach’s Alpha. Data obtained from a purposive sample of 80 teachers were analyzed using multiple linear regression (MLR) to test the relationships between variables. Based on the results, a 16-week strategic plan was implemented across the university, with its impact assessed using a paired-sample t-test. Results: MLR results showed that all five variables had a significant positive effect on student loyalty (p < 0.05), with image (β = 0.298) and student satisfaction (β = 0.294) having the strongest impact. The paired-sample t-test revealed significant improvements across all variables, including loyalty, after the strategic plan. Conclusions: This study contributes to the understanding of loyalty-building in higher education by demonstrating that targeted improvements in satisfaction, image, commitment, service quality, and sustainability enhance loyalty. The findings provide actionable insights for improving student retention through targeted institutional development.